Discharge planning from hospital - Gonçalves-Bradley, DC; Lannin, NA; Clemson, L; Cameron, ID; Shepperd, S (Cochrane Collaboration, 2022)
Background: Discharge planning is a routine feature of health systems in many countries that aims to reduce delayed discharge from hospital, and improve the co‐ordination of services following discharge from hospital and reduce the risk of hospital readmission. This is the fifth update of the original review.